A phase 1/2a safety, pharmacokinetics, and efficacy study of the novel nucleoside analog FF‐10502‐01 for the treatment of advanced solid tumors. Issue 10 (7th March 2023) - Janku, Filip; Javle, Milind M.; Sen, Shiraj; Pant, Shubham; Bramwell, Lindsay G.; Subbiah, Vivek; Way, Tracey; Wages, David S.; Wheeler, Catherine A.; Suzuki, Takeaki; Saeki, Kazunori; Subach, Ruth Ann; et al.
Abstract: Background: The nucleoside FF‐10502‐01, structurally similar to but with different biologic effects than gemcitabine, shows promising activity both alone and combined with cisplatin in preclinical gemcitabine‐resistant tumor models. We conducted an open‐label, single‐arm, 3 + 3 first‐in‐human trial to explore the safety, tolerability, and antitumor activity of FF‐10502‐01 in patients with solid tumors. Methods: Patients with inoperable metastatic tumors refractory to standard therapies were enrolled. Escalating intravenous FF‐10502‐01 doses (8–135 mg/m 2 ) were administered weekly for 3 weeks in 28‐day cycles until progressive disease or unacceptable toxicity was observed. Three expansion cohorts were subsequently evaluated. Results: A phase 2 dose of 90 mg/m 2 was determined after evaluating 40 patients. Dose‐limiting toxicities included hypotension and nausea. Phase 2a enrolled patients with cholangiocarcinoma (36), gallbladder cancer (10), and pancreatic/other tumors (20). Common adverse events were grade 1–2 rash, pruritus, fever, and fatigue. Grade 3 or 4 hematologic toxicities were observed at low incidences, including thrombocytopenia (5.1%) and neutropenia (2%). Confirmed partial responses (PRs) occurred in five patients with gemcitabine‐refractory tumors, including three with cholangiocarcinoma and one each with gallbladder and urothelial cancer. Median progression‐free and overall survival rates in patients with cholangiocarcinoma were 24.7 and 39.1 weeks, respectively. Prolonged progression‐free survival in patients with cholangiocarcinoma was associated with BAP1 and PBRM1 mutations. Conclusion: FF‐10502‐01 was well tolerated with manageable side effects and limited hematologic toxicity. Durable PRs and disease stabilizations were observed in heavily pretreated biliary tract patients who had received prior gemcitabine. FF‐10502‐01 is distinct from gemcitabine and may represent an effective therapy. Abstract : A phase 1/2a study of FF‐10502‐01, a nucleoside structurally similar to gemcitabine but with distinct biologic effects, demonstrates activity in patients with gemcitabine‐refractory tumors, including cholangiocarcinoma; this compares favorably to second‐line FOLFOX chemotherapy in patients with advanced biliary cancer. Prolonged progression‐free survival in cholangiocarcinoma was associated with BAP1 and PBRM1 mutations, which may be important for patient selection.